2022
DOI: 10.3389/fped.2022.997196
|View full text |Cite
|
Sign up to set email alerts
|

Redo laparoscopic pyeloplasty for recurrent ureteropelvic junction obstruction: Propensity score matched analyses of a high-volume center

Abstract: PurposeReview the experience of redo laparoscopic pyeloplasty (RLP) in patients with recurrent ureteropelvic junction obstruction (UPJO) in comparison to primary laparoscopic pyeloplasty (PLP) and redo open pyeloplasty (ROP), and determine the feasibility and effectiveness of RLP for recurrent UPJO in children.MethodsWe retrospectively reviewed the clinical data of patients treated with transperitoneal PLP, RLP, and ROP for UPJO from December 2015 to December 2022. The Propensity score matching (PSM) was used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…However, it is observed that approximately 2.5–10% of patients experience relapse after the initial operation [ 10 ]. Moreover, it is important to note that the recurrence rate of actual surgery may be higher due to insufficient follow-up time [ 11 ]. This study aims to investigate the causes of recurrent stenosis after primary LP for ureteropelvic junction obstruction.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is observed that approximately 2.5–10% of patients experience relapse after the initial operation [ 10 ]. Moreover, it is important to note that the recurrence rate of actual surgery may be higher due to insufficient follow-up time [ 11 ]. This study aims to investigate the causes of recurrent stenosis after primary LP for ureteropelvic junction obstruction.…”
Section: Introductionmentioning
confidence: 99%